2020
DOI: 10.1101/2020.03.20.20039495
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Global profiling of SARS-CoV-2 specific IgG/ IgM responses of convalescents using a proteome microarray

Abstract: COVID-19 is caused by SARS-CoV-2, and has become a global pandemic. There is no highly effective medicine or vaccine, most of the patients were recovered by their own immune response, especially the virus specific IgG and IgM responses. However, the IgG/ IgM responses is barely known. To enable the global understanding of SARS-CoV-2 specific IgG/ IgM responses, a SARS-CoV-2 proteome microarray with 18 out of the 28 predicted proteins was constructed. The microarray was applied to profile the IgG/ IgM responses… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
66
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(72 citation statements)
references
References 48 publications
5
66
0
1
Order By: Relevance
“…COVA1-21 also efficiently blocked virus infection, suggesting an alternative mechanism of neutralization than blocking ACE2 engagement. Overall, our data are consistent with the previous identification of multiple antigenic RBD sites for SARS-CoV-2 and additional non-RBD sites on the S protein as described for SARS-CoV and MERS-CoV (29,38). Here, our discovery of non-RBD-targeting mAbs provides additional depth to the definition of antibody epitopes on the SARS-CoV-2 S protein.…”
Section: A and B) With 7 Mabs (22%) Showing Cross-binding To Sars-supporting
confidence: 92%
“…COVA1-21 also efficiently blocked virus infection, suggesting an alternative mechanism of neutralization than blocking ACE2 engagement. Overall, our data are consistent with the previous identification of multiple antigenic RBD sites for SARS-CoV-2 and additional non-RBD sites on the S protein as described for SARS-CoV and MERS-CoV (29,38). Here, our discovery of non-RBD-targeting mAbs provides additional depth to the definition of antibody epitopes on the SARS-CoV-2 S protein.…”
Section: A and B) With 7 Mabs (22%) Showing Cross-binding To Sars-supporting
confidence: 92%
“…Overall, these data fit very well with the observation that most humoral immune responses against SARS-CoV-2 and other human coronaviruses are directed against the S and N proteins (Farrera et al, 2020;Jiang et al, 2020;Poh et al, 2020). These results also support the notion that the selective pressure exerted by the human antibody response is already detectable in the SARS-CoV-2 population.…”
Section: Antigenic Variability Of Sars-cov-2 Proteinssupporting
confidence: 85%
“…These works, as well as others (Farrera et al, 2020;Poh et al, 2020), revealed that the cell-mediated responses against SARS-CoV-2 are not restricted to the nucleocapsid (N) and spike (S) proteins, but rather target both structural and non-structural viral products. In parallel, analyses of B cell responses in SARS-CoV-2 infected patients showed that the S and N proteins are the major target of the antibody response and identified specific B cell epitopes in the S protein (Farrera et al, 2020;Jiang et al, 2020;Poh et al, 2020). We exploited this growing wealth of information to investigate whether, after a few months of sustained transmission, the selective pressure exerted by the human adaptive immune response is already detectable in the SARS-CoV-2 population and to investigate how the virus is evolving in response to such a pressure.…”
Section: Introductionmentioning
confidence: 97%
“…In hospitalized patients, seroconversion is typically detected between 5-14 days post symptom onset, with a median time of 5-12 days for anti-S IgM and 14 days for IgG and IgA 6,7,[13][14][15][16] . The kinetics of anti-N response was described to be similar to that of anti-S, although N responses might appear earlier [15][16][17] . Anti-SARS-CoV-2 antibody titers correlate with disease severity, likely reflecting higher viral replication rates and/or immune activation in patients with severe outcome.…”
Section: Introductionmentioning
confidence: 94%
“…Anti-SARS-CoV-2 antibody titers correlate with disease severity, likely reflecting higher viral replication rates and/or immune activation in patients with severe outcome. Besides N and S, antibody responses to other viral proteins (mainly ORF9b and NSP5) were also identified by antibody microarray 17 .…”
Section: Introductionmentioning
confidence: 99%